2018
DOI: 10.1093/bioinformatics/bty043
|View full text |Cite
|
Sign up to set email alerts
|

Accurity: accurate tumor purity and ploidy inference from tumor-normal WGS data by jointly modelling somatic copy number alterations and heterozygous germline single-nucleotide-variants

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…For deletion, the integer copy number values corresponding to 5%, 10%, and 15% were 1.47, 1.65, and 1.80 copies, respectively. Although ABSOLUTE is widely used for estimating the ploidy and purity of samples, this algorithm tends to overestimate ploidy [30]. Thus, in this study, we chose 10% values corresponding to 3.07 copies and 1.65 copies for amplification and deletion, respectively, after considering overestimation, although this threshold may be rather strict.…”
Section: Resultsmentioning
confidence: 99%
“…For deletion, the integer copy number values corresponding to 5%, 10%, and 15% were 1.47, 1.65, and 1.80 copies, respectively. Although ABSOLUTE is widely used for estimating the ploidy and purity of samples, this algorithm tends to overestimate ploidy [30]. Thus, in this study, we chose 10% values corresponding to 3.07 copies and 1.65 copies for amplification and deletion, respectively, after considering overestimation, although this threshold may be rather strict.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Our study also showed high-purity group had more CNA events among all chromosomal locations. According to a previous study, 13 power to detect CNAs is highly dependent on the tumor purity, because that large fraction of copy-neutral DNA from noncancerous cells in low-purity tumors will significantly decrease the signal/noise ratio of CNAs. The results of our study have validated this point.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been proposed for tumor purity prediction, such as CONSENSUS [15] and ESTIMATE [14]. Other methods for tumor purity predictions consider methylation data [1113] and copy number variation [8, 36, 37]. Most non-genomic (e.g., transcriptome- or methylome-based) purity prediction methods consider a subset of preselected stromal-cell-expressed genes or stromal-cell-specific methylation loci as predictors.…”
Section: Discussionmentioning
confidence: 99%